Chapter 16 Regulated Market Socialism - Lane, David (Bristol University Press, 2023)
The digital PDF and EPUB versions of Chapters 3 and 16 are available Open Access and distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 licence (https://creativecommons.org/licenses/by-nc-nd/4.0). Since the world economic crisis of 2007, commentators have pointed to the dangers of a capitalistic system that seems incapable of delivering sustainable growth and well-being. This bold new book offers an exhaustive diagnosis of global capitalism across the world's nations. David Lane examines the nature and appeal of neoliberal capitalism according to different schools of thought, and he analyses proposals for its reform and replacement from state socialism and social democratic corporatism to self-sustaining networks. Looking ahead to a novel system of economic and political coordination based on a combination of market socialism and state planning, this book offers crucial insights for scholars thinking about alternatives to capitalism.